The Concept of the Principle of Non-Refoulement in Refugee Law (Discourse of Law and Administration, 2022)
This article concerns a fundamental principle of the prohibition of refoulement in international refugee law, in reference also to European law and national regulations. In general, the principle of non-refoulement forbids expulsion of foreign nationals beyond borders of a state in which they are seeking protection on humanitarian grounds, and it is a fundamental standard of protection of refugees. The article presents how this principle functions as a standard for international protection, including its functions of guaranteeing comprehensive refugee protection. In the methodological aspect, a legal dogmatic method, a comparative legal method as well as the system analysis and the content analysis of legal texts, have been used. This article presents in an innovative way the approach to the principle of non-refoulement, not only as a standard of protection, but also, through the presentation of its function, by raising some questions concerning the modification of the form of refugee protection in favour of humanitarian protection on the basis of this principle. This issue is the main thesis of this article. This is of particular importance for the future development of refugee law as well as a migration and asylum policy.
Keywords: refugee protection; the principle of non-refoulement; international refugee law; human rights